Recent Approaches for Chemical Speciation and Analysis by Electrospray Ionization (ESI) Mass Spectrometry - Indelicato, Serena; Bongiorno, David; Ceraulo, Leopoldo (Frontiers in Chemistry, 2021)
In these latest years, the chemical speciation of several species has been increasingly monitored and investigated by means of electrospray ionization mass spectrometry (ES-MS). This soft ionization technique is capable to gently take into the gas phase metal-ligand complexes and gather a wealth of information on their energetics, shape, and fragmentation pathways. For this reason, this technique is frequently chosen in a synergistic approach to investigate competitive ligand exchange-adsorptive other ways analyzed by cathodic stripping voltammetry (CLE-ACSV). ESI-MS analyses require a careful experimental design as they may be impacted by instrumental artifacts such as ESI adduct formation, fragmentation, and sometimes reduction reactions. Furthermore, ESI source differences of ionization efficiencies among the detected species can be misleading. In this mini-review, we collected and critically reported the most recent approaches adopted to mitigate or eliminate these drawbacks and show the potential of this ionization technique that complemented by quantum mechanical information, coupled with ion mobility sectors or simply used in tandem mass spectrometry experiments is capable to provide unique information from the gas phase complexes up to metallomics.